Knowledge and awareness of high blood pressure in Ward F, Ifako-Ijaiye local government area, Lagos State, Nigeria - Y.T. Akindele; O.O. Ayankogbe (South African Family Practice)
Objectives: In Nigeria, most people living with an elevated blood pressure are unaware of it until they suffer complications. The aim of this study was to determine levels of awareness of high blood pressure in Ward F, Ifako-Ijaiye local government area, Lagos, Nigeria.